2012
DOI: 10.1097/jto.0b013e3182745948
|View full text |Cite
|
Sign up to set email alerts
|

Local Ablative Therapy of Oligoprogressive Disease Prolongs Disease Control by Tyrosine Kinase Inhibitors in Oncogene-Addicted Non–Small-Cell Lung Cancer

Abstract: Introduction Many patients with oncogene driven non-small cell lung cancer treated with TKIs experience limited sites of disease progression. This study investigated retrospectively the benefits of local ablative therapy (LAT) to CNS and/or limited systemic disease progression and continuation of crizotinib or erlotinib in patients with metastatic ALK gene rearrangement (ALK+) or EGFR-mutant (EGFR-MT) NSCLC, respectively. Materials and Methods Patients with metastatic ALK+ NSCLC treated with crizotinib (n=38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
441
1
11

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 598 publications
(483 citation statements)
references
References 54 publications
15
441
1
11
Order By: Relevance
“…However, most patients will eventually progress within 8–11 months, either in the brain and/or extra‐cranial sites, as was the case with our patient 4, 5. There is evidence suggesting that NSCLC patients with actionable mutations in the ALK or EGFR genes may have a longer progression‐free survival if they are kept on targeted therapy while efforts to control oligometastases by other means are taken 6. In theory, resistant clones could be eradicated with local therapies, thus allowing for continued effectiveness of targeted therapy.…”
Section: Discussionsupporting
confidence: 56%
“…However, most patients will eventually progress within 8–11 months, either in the brain and/or extra‐cranial sites, as was the case with our patient 4, 5. There is evidence suggesting that NSCLC patients with actionable mutations in the ALK or EGFR genes may have a longer progression‐free survival if they are kept on targeted therapy while efforts to control oligometastases by other means are taken 6. In theory, resistant clones could be eradicated with local therapies, thus allowing for continued effectiveness of targeted therapy.…”
Section: Discussionsupporting
confidence: 56%
“…63 For example, one study showed that for 46% of patients on crizotinib, the CNS represents the site of first progression, and that the CNS was the sole site of progression in 85% of these patients. 69 It was also shown, at least in one case report, that less than 0.3% of the plasma concentration of crizotinib enters the cerebrospinal fluid, indicating that crizotinib may not present at therapeutic concentrations in the brain. 70 The activity of a drug in the brain, especially in diseases with a high rate of brain metastases, such as NSCLC, may be better addressed in future trials through defining separate cohorts of patients with specific oncogenic driver and CNS disease, and adding those cohorts to the earliest phase I studies of the relevant molecularly targeted therapies.…”
Section: Issues In Specific Tumor Typesmentioning
confidence: 99%
“…It is thought that radiation can increase the permeability of the blood–brain barrier, thereby rendering TKI more effective. One retrospective study showed that patients with only intracranial progression had a continued mPFS of 7.1 months when resumed on crizotinib post-radiation [65]. While it is generally recommended to continue the same TKI post-radiation, the benefit of switching TKI at that time has not been specifically addressed.…”
Section: Localized Therapy For Brain Metastasesmentioning
confidence: 99%